Kajian Materi Shalat pada Kitab Mabadi’ul Fiqhiyyah Juz II dan Fiqh Kementerian Agama RI di MI Nahdlatussalam Anjir Serapat Kabupaten Kuala Kapuas - Muhammad Fadilah; Rofi'i Rofi'i (Al-Mudarris, 2019)
Fiqh material about prayer which is very important and becomes the main principle for students in carrying out daily worship, especially prayer. among them is using the book Mabadi'ul Fiqhiyyah Juz II. Book Mabadi'ul Fiqhiyyah Juz II is one indicator that is very important for the knowledge of students who are just learning in understanding fiqh. The book is also one of the characteristics of MI Nahdlatussalam which has salafi education and collaboration with general education which also teaches fiqh books of the Indonesian Ministry of Religion. The purpose of this study is (1) to describe the material of prayer in the book of Mabadi'ul Fiqhiyyah Juz II with fiqh material of the Ministry of Religion's curriculum. This study uses descriptive qualitative methods that were extracted through interview data and documentation. The results showed that: (1) The material for prayer in the Mabadi'ul Fiqhiyyah Juz II discusses about: the obligatory conditions of prayer, the legal requirements for prayer, prayer of fardhu and its time, sunnah prayer which follows the prayer of fardhu, the times that are forbidden to pray, the pillars of prayer, sunnah-sunnah in prayer, and things that cancel prayer. While the subject matter of the fiqh curriculum of the Ministry of Religion of the Republic of Indonesia discusses: the obligatory conditions of prayer, the legal requirements for prayer, the pillars of prayer, the sunnahs in prayer, and the things that cancel prayer.